Ion radiation albedo effect: influence of surface roughness on ion implantation and sputtering of materials. (8th December 2016) - Li, Yonggang; Yang, Yang; Short, Michael P.; Ding, Zejun; Zeng, Zhi; Li, Ju
Abstract: In fusion devices, ion retention and sputtering of materials are major concerns in the selection of compatible plasma-facing materials (PFMs), especially in the context of their microstructural conditions and surface morphologies. We demonstrate how surface roughness changes ion implantation and sputtering of materials under energetic ion irradiation. Using a new, sophisticated 3D Monte Carlo (MC) code, IM3D, and a random rough surface model, ion implantation and the sputtering yields of tungsten (W) with a surface roughness varying between 0–2 µ m have been studied for irradiation by 0.1–1 keV D +, He + and Ar + ions. It is found that both ion backscattering and sputtering yields decrease with increasing roughness; this is hereafter called the ion radiation albedo effect. This effect is mainly dominated by the direct, line-of-sight deposition of a fraction of emitted atoms onto neighboring asperities. Backscattering and sputtering increase with more oblique irradiation angles. We propose a simple analytical formula to relate rough-surface and smooth-surface results.